AVAILABILITY OF ACCESS, WATCH, AND RESERVE GROUP ANTIBIOTICS IN PHARMACIES SURROUNDING TERTIARY HOSPITALS IN CHITWAN, NEPAL - Chaurasiya, Roshan (Journal of Chitwan Medical College, 2024)
Background: Antimicrobial resistance, a global health challenge, threatens the effective prevention and treatment of infections caused by bacteria, fungi, parasites and viruses no longer susceptible to the common medicines used to treat them. AMR can render infections challenging to treat, leading to severe illness and potential fatalities. Present study was conducted to investigate the availability of Access, Watch, and Reserve (AWaRe) group antibiotics in pharmacies proximal to tertiary hospitals in Chitwan, Nepal.Methods: The study employed a descriptive cross-sectional design with a quantitative approach, focusing on demographic and awareness variables as independent factors and the availability of AWaRe group antibiotics as the dependent variable. Conducted in Bharatpur, Chitwan, Nepal, the research targeted pharmacies within a 2 km radius of Chitwan Medical College, totaling 96 pharmacies, utilizing a complete enumeration technique for sampling. Data collection involved structured questionnaires and observational checklists. Ethical consideration was followed throughout the study.Results: The study’s findings regarding the AWaRe classification reveal that Access and Watch antibiotics collectively constitute 45% of the total antibiotics surveyed. This indicates a substantial reliance on these categories for treatment in the region. Notably, Reserve antibiotics, vital for serious infections, represent 24% of the surveyed antibiotics, suggesting a significant consideration for their judicious use amidst their lower availability compared to Access and Watch antibiotics.Conclusions: Findings from this study are expected to contribute valuable insights into the antibiotic landscape in the study area, offering recommendations for enhancing the rational use of antibiotics and combating antimicrobial resistance.